Formation of Scattering Characteristics for Acoustical Ray Tracing Simulation - Srđan BOJIČIĆ; Dragana ŠUMARAC-PAVLOVIĆ; Miomir MIJIĆ (Archives of Acoustics)
Ray tracing simulation of sound field in rooms is a common tool in room acoustic design for predicting impulse response. There are numerous commercial engineering tools utilising ray tracing simulation. A specific problem in the simulation is the modelling of diffuse reflections when contribution of individual surface is prevailing. The paper introduces modelling of scattering which is interesting when the whole impulse response of a room is not a goal but contribution of certain surface. The main goal of the project is to shape directivity characteristics of scattered reflection. Also, an innovative approach is suggested for converting the energy histogram information obtained by ray tracing into an “equivalent impulse response”. The proposed algorithm is tested by comparing the results with measurements in a real sound field, realised in a scaled model where a diffusing surface is hardware-implemented.